Mapping seasonal sentiments of people visiting blue spaces in urban wetlands: A pilot study on inland cities of China - Li, Yanjiao; Sun, Yuxiang; Zhao, Yan; Wang, Yang; Cheng, Shiping (Frontiers in Ecology and Evolution, 2022)
To evoke positive human emotions is a critical service of blue spaces in urban wetland parks, but it is still scarce about spatiotemporal distribution of exposed emotions induced by perceptions of wetlands with different levels in joint landscape and microclimate. In this study, thirty urban wetland parks were selected from 17 cities in Central China, where a total of 1184 portrait photos of visitors were obtained from a social network platform (Sina Weibo) to analyze their exposed sentiments by rating facial expression scores of happy and sad emotions and net positive emotion index (NPE; happy-score minus sad-score) in 2020. Landscape metrics were remotely evaluated for every wetland park, where microclimatic factors were recorded in days when photos were exposed. Based on regressions of the park level data, blue-space area can be perceived as a positive driver to expose happiness in spring (regression coefficient [RC] of 0.20), but it generated negative contributions to exposed NPE in autumn (RC of -2.98). The high elevation benefitted the presentation of positive emotions in summer and autumn (RC of 1.35×10-3), but extreme daily temperature, air humidity, and wind velocity were together perceived to expose sadness (RC of 0.11, 0.03, and 0.51, respectively). It was indicated on mapped distribution that blue-space visits can evoke more smiles in wetland parks of northern Hunan, southern Hubei, and eastern Anhui in spring. Blue spaces in Shanxi and northwestern Hebei were recommended to be visited if better moods were expected in autumn. Small-area blue spaces in wetlands at higher elevations were recommended for nature experiencers in warm seasons to reduce the risk that sadness was elicited.